Reformasi Koperasi Terhadap Corporate Governance : Kasus Pada Koperasi Simpan Pinjam - Siti Rosmayati (Universitas Koperasi Indonesia, 2022)
This paper tries to determine the effect of cooperative reform on corporate governance in savings and loan cooperatives in Cimahi City, which has carried out various cooperative reforms towards the digital era that aims to improve corporate governance. So far, there is limited information regarding the results of some previous studies. The purpose of this study is to determine the effect of cooperative reform towards the digital era on corporate governance. This study adopted a correlational research design. The research sample is 100 cooperative members taken in January 2022. The constant in the research case is 0.184 and beta1 = 0.698, F is reform in the field of cooperatives and e is the standard error. Therefore, reforms in the cooperative sector affect Corporate Governance because the value of beta1 = 0.698≠0.. Descriptive and inferential statistics are used. The hypothesis was tested using a simple regression coefficient at a confidence level of 90%. This study reveals that cooperative reform has a significant effect on Corporate Governance. The study recommends that cooperatives should determine how to fully adopt reforms. The findings of this study can help scholars and policy makers to understand and formulate policies on reform.